BIMBINGAN BAGI ANAK CERDAS DAN ANAK BERBAKAT DI SD ISLAM COKRO AMINOTO 1 KALABAHI - Juliana Albertina Mayopu; Jesenia Loriance Alelang, Imanuel Musa Laukamang, Lala Enggadina Moilegi, Yessy Mata, Petrus Mau Tel (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
Child education requires an adaptive approach tailored to the needs and potential of each child. This article discusses the educational strategies for gifted and talented children implemented by a teacher named Mr. Alwi at Cokroaminoto I Islamic Elementary School. The main focus is on differentiating approaches to gifted and talented children, as well as effective collaboration between teachers and parents in guiding children's development. Strategies for handling active children who are often considered